DYNAMICS OF THE POULTRY MARKET IN GHANA - Onumah, Edward Ebo; Ayeduvor, Selorm (Journal of Agricultural Sciences (Belgrade), 2023)
This paper examines the dynamics of poultry-market in Ghana using secondary data and field survey from four regions including Greater Accra, Ashanti, Northern, and Western. It considers trend and content analysis to highlighting specific products imported, source, drivers, and potential for domestic poultry to substitute for imports. The paper confirms that Ghana imports about 80% of poultry meat mostly in the form of branded cut parts (thighs, wings, legs, back, and offal) from high income countries including Belgium, US, Brazil, Poland, and Netherlands. Despite 35% increase in tariffs, imported poultry meat tend to be 27-30% cheaper than locally produced chicken. Finding further shows that though there is some preference for domestic poultry meat, this does not translate into purchase decisions due to preference for handier and ready-to-use products. The paper recommends prioritization of policies to boost local production through investment in processing (cut parts), packaging into brands, and marketing facilities such as cold vans. Further, policies to reduce chicken meat import volumes may be focused on other non-tariff measures such as licenses, allotments, trade embargoes, foreign exchange restrictions, and import depositaries.